Effect of high-voltage electrostatic field on post-harvest quality of cut roses - Li Wang; Yuan Han; Ying Zhang; Zijian Feng; Shuyi Wei (Journal of Plant Interactions)
Traditional fresh-cut flower preservation technology mainly uses a combination of chemical agents and low-temperature refrigeration, resulting in high energy consumption and environmental pollution. The research was based on the exploration of the effect of high-voltage electrostatic field on the preservation effect of rose cut flowers. By setting the gradient field strength to 10, 30 and 50 kV/m, the treatment was conducted for 2 hours a day for 3 consecutive days. The morphological changes, vase life, and related physiological indicators of cut roses were recorded throughout the process. The results showed that 10 kV/ m can significantly extend the vase life of cut roses. The application of this technology will provide a new idea for the preservation of fresh cut flowers.